Optical properties of armchair graphene nanoribbons under uniaxial strain. Issue 6 (22nd April 2014) - Jia, Yonglei; Gao, Yang
<x xml:space="preserve">Abstract</x> The optical properties of armchair graphene nanoribbons (AGNRs) under the uniaxial strain are studied within a non‐orthogonal tight‐binding model. For 9‐AGNR and 10‐AGNR, the first transition energy <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghgzchp0p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />E11</alternatives> increases and the second one <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghgzchpqj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />E22</alternatives> decreases when the uniaxial strain increases. And for 10‐AGNR, there is a crossover for the two transition energies under the uniaxial strain. While for 11‐AGNR, the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghgzchpnh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />E11</alternatives> transition energy decreases firstly and then increases and the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghgzchpw4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />E22</alternatives> transition energy increases when the uniaxial strain increases. Interestingly, there is a semiconductor–metal transition for 11‐AGNR with increasing strain. These variations of the optical transition energies can be used as a supplemented tool to detect the deformation degree of an AGNR under the uniaxial strain.